2017
DOI: 10.3390/en10071064
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Non-Equilibrium Thermodynamics and Reactive Transport to Model CH4 Production from the Nankai Trough Gas Hydrate Reservoir

Abstract: Abstract:The ongoing search for new sources of energy has brought natural gas hydrate (NGH) reservoirs to the forefront of attention in both academia and the industry. The amount of gas reserves trapped within these reservoirs surpasses all of the conventional fossil fuel sources explored so far, which makes it of utmost importance to predict their production potential and safety. One of the challenges facing those attempting to analyse their behaviour is that the large number of involved phases make NGHs unab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Two pressure sensors are connected to the pipe at the top and bottom of the container for the measurement of the system pressure. horizontal well, Qorbani et al [9] suggested a slightly higher hydrate decomposition rate with the former well pattern than the later. From these studies, it is easy to recognize that there are few studies focusing on the effects of the application of different exploitation methods on NGH production in a vertical well, especially aiming at the in-situ electric heating without mass injection and the comparison of production effects in different depressurization and heating modes.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Two pressure sensors are connected to the pipe at the top and bottom of the container for the measurement of the system pressure. horizontal well, Qorbani et al [9] suggested a slightly higher hydrate decomposition rate with the former well pattern than the later. From these studies, it is easy to recognize that there are few studies focusing on the effects of the application of different exploitation methods on NGH production in a vertical well, especially aiming at the in-situ electric heating without mass injection and the comparison of production effects in different depressurization and heating modes.…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, they also thought the mass and heat transfer mainly dominated the hydrate decomposition by depressurization in the pilot-scale simulator. Besides, after the comparison of NGH exploitation in a vertical well with that in a horizontal well, Qorbani et al [9] suggested a slightly higher hydrate decomposition rate with the former well pattern than the later.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations